The Influence of the Doctrine of a Mursyid (Case Study of Suluk Di Mudi Bireuen Aceh - Fahmi Fahmi; Amroeni Drajat; Hasan Bakti Nasution (Budapest International Research and Critics University, 2022)
The doctrines carried out by Mursyid to the santri / congregation of Suluk are taboos on tawajjuh worship, abstinence from bloody food, daily and weekly remembrance by multiplying remembrance up to 70,000 times, after praying the remembrance must be read 200 times until it pays off 70,000. The influence of the Suluk mursyid doctrine on the students of MUDI Bireun, namely the influence on the positive attitude of the personality of the santri, the influence on the social attitudes of the community and the influence on the knowledge of students about Suluk worship. After the prayer, it is obligatory to read dhikr 200 times until it pays off 70,000. The influence of the Suluk mursyid doctrine on the students of MUDI Bireun, namely the influence on the positive attitude of the personality of the santri, the influence on the social attitudes of the community and the influence on the knowledge of students about Suluk worship. After the prayer, it is obligatory to read dhikr 200 times until it pays off 70,000. The influence of the Suluk mursyid doctrine on the students of MUDI Bireun, namely the influence on the positive attitude of the personality of the santri, the influence on the social attitudes of the community and the influence on the knowledge of students about Suluk worship.